Common Listening Challenges: Indonesian EFL Learners’ Perception - Lidiyatul Izzah; Khodijah Keeya (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2019)
Being a major part of internationalizing higher education, teaching English taps particular general cognitive abilities. It is mainly regarding listening that is hypothesized to have a higher influence on acquisition of foreign language. The aim of this study was to identify the common listening challenges experienced by Indonesian EFL learners. This research was practical research using descriptive methods of quantitative research. Subject of the study were subsequently randomly chosen, in which EFL learners at even semesters become the representative. In collecting data, the researchers used a self-structured questionnaire that refers to three primary categories: (1) the listener, (2) the passage, and (3), the physical setting. The data was then statistically evaluated by referring to Likert type scales, to discover useful information. After all, the finding showed that distortions, lexis recognition, phonological awareness, complexity of the passage and the speech rate highlighted a high degree response of common listening challenges. The significance of the study expected to contribute learners with a better understanding and propose new ideas for acceptable teaching listening.